Reliance on long-term care as a “new” social risk in national and EU law - Strban, Grega; Bagari, Sara (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
There have always been people who cannot take care of their daily needs and are reliant on care. However, due to higher life expectancy and low birth rates, changes in lifestyle and increased mobility, reliance on long-term care is becoming a general risk in life. Therefore, it must be provided with social protection. In this respect, the criteria for shaping the (new) social risk of reliance on long-term care are also fulfilled. Although different benefits are already provided within different parts of the social security system, the paper discusses that the best option is to define reliance on long-term care as an independent social risk. Furthermore, we must ensure that providing long-term care will not turn out to be a double social risk. The issue has to be addressed at the national and at the EU level.
Keywords: social risk; long-term care; reliance on long-term care; national law; EU law